Sensitive Chandra coverage of a representative sample of weak-line quasars: revealing the full range of X-ray properties. Issue 4 (16th February 2022) - Ni, Q; Brandt, W N; Luo, B; Garmire, G P; Hall, P B; Plotkin, R M; Shemmer, O; Timlin, J D; Vito, F; Wu, J; Yi, W
ABSTRACT: We present deeper Chandra observations for weak-line quasars (WLQs) in a representative sample that previously had limited X-ray constraints, and perform X-ray photometric analyses to reveal the full range of X-ray properties of WLQs. Only 5 of the 32 WLQs included in this representative sample remain X-ray undetected after these observations, and a stacking analysis shows that these 5 have an average X-ray weakness factor of >85. One of the WLQs in the sample that was known to have extreme X-ray variability, SDSS J1539+3954, exhibited dramatic X-ray variability again: it changed from an X-ray normal state to an X-ray weak state within ≈3 months in the rest frame. This short time-scale for an X-ray flux variation by a factor of ≳9 further supports the thick disc and outflow (TDO) model proposed to explain the X-ray and multiwavelength properties of WLQs. The overall distribution of the X-ray-to-optical properties of WLQs suggests that the TDO has an average covering factor of the X-ray emitting region of ∼0.5, and the column density of the TDO can range from $N_{\rm H}\, \sim 10^{23-24}~{\rm cm}^{-2}$ to $N_{\rm H}\, \gtrsim 10^{24}~{\rm cm}^{-2}$, which leads to different levels of absorption and Compton reflection (and/or scattering) among WLQs.